Derivatization and combination therapy of current COVID-19 therapeutic agents: a review of mechanistic pathways, adverse effects, and binding sites. Issue 10 (October 2020) - El Kantar, Sally; Nehmeh, Bilal; Saad, Philippe; Mitri, Gabie; Estephan, Celine; Mroueh, Mohamad; Akoury, Elias; Taleb, Robin I.
Graphical abstract: Highlights: We summarized the mechanisms of action of 11 repurposed drugs for COVID-19 treatment. We reviewed clinical trials performed on drugs to treat COVID-19 patients. We proposed combination therapy using current COVID-19 repurposed drugs. Repurposed drugs have side effects and could be ineffective when the virus mutates. We proposed drug derivatives with potentially enhanced activity against COVID-19. Abstract : Current treatment of patients with coronavirus 2019 (COVID-19) involves repurposed drugs that inhibit viral infection by either binding to their respective targets or via modulating cellular signal transduction. However, there is still a great deal of efficacy enhancement through combination therapy and derivatization. Combination therapy should involve agents with significant activity and different mechanisms of action. The structural map of the interaction between a drug and its target protein will help guide drug discovery for devising safe and effective ways to treat COVID-19. Herein, we report numerous synthetic designs based on enhanced affinity to the viral carbohydrate-rich protein spikes and protein-binding sites of COVID-19. Teaser: We report the structural design of several analogs of current COVID-19 repurposed drugs. These analogs are designed to enhance the drug affinity to either the protein-binding sites or to the viral protein spikes.